2010
DOI: 10.1590/s1808-86942010000400013
|View full text |Cite
|
Sign up to set email alerts
|

Estudo normativo dos parâmetros acústicos vocais de crianças de 4 a 12 anos de idade sem sintomas vocais: estudo piloto

Abstract: Acoust ic vocal analysis is a simple and fast method that allows to differentiate normal from changed voices. There are few studies that analyze normal acoustic vocal parameters at different age ranges in children. Aims:To establish normative acoustic parameters of children's voice aged 4 to 12 years. Methods:Two hundred and forty children were divided into four sub-groups by age: G1 (n-60; 4-5 years), G2 (n-60; 6-7 years), G3 (n-60; 8-9 years) and G4 (n-60; 10-12 years). The children's parents answered a ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 15 publications
0
11
0
5
Order By: Relevance
“…It must also be remembered that, in addition to possible physiological impacts, warm-up offers a mental function, providing focus and concentration for the activity to follow. Studies conducted with children observed that the average Brazilian fundamental frequency (f0) of children's voices, in the 8 to 12 years age group, ranges from 230 to 236 Hz (9,13) . In this study, the fundamental frequency prior to vocal warm-up was close to this average.…”
Section: Discussionmentioning
confidence: 99%
“…It must also be remembered that, in addition to possible physiological impacts, warm-up offers a mental function, providing focus and concentration for the activity to follow. Studies conducted with children observed that the average Brazilian fundamental frequency (f0) of children's voices, in the 8 to 12 years age group, ranges from 230 to 236 Hz (9,13) . In this study, the fundamental frequency prior to vocal warm-up was close to this average.…”
Section: Discussionmentioning
confidence: 99%
“…The study's inclusion criteria encompassed all the vocal registers of children with no voice complaints, enrolled in a preschool, aged 6 to 8 years -which was the age of those who attended the institution where the study was carried out. Also, restricting the age range allowed for a more biologically homogeneous sample, considering the growth and development of the larynx and vocal tract, when the anatomical conditions of the larynx are similar (keeping in mind the quick changes that take place in these structures) and the differences between the sexes are not yet significant 1,5,7,17,18 . Due to these quick differentiations in the morphology of the vocal tract and consequently the voice quality, other studies have also researched restricted age groups 8,18 .…”
Section: Methodsmentioning
confidence: 99%
“…One of these is taking too long to seek help from health professionals, due to little concern on the part of the parents regarding their child's voice changes, as the children do not have quite alarming symptoms involving other systems 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Na infância, as alterações de voz podem afetar os desempenhos escolares, sociais e emocionais, podendo também refletir problemas no desenvolvimento da capacidade de comunicação na vida adulta (Tavares, Labio, & Martins, 2010).…”
Section: Introductionunclassified